Disrupting comfort: From low-carbon to low-impact cities - De Castro Mazarro, Alejandro; Joshi, Neelakshi; Samartzidis, Lasare (Raumforschung und Raumordnung | Spatial Research and Planning, 2024)
In this commentary, we argue for the low-impact city as an alternative to the dominant urban imaginary of the low-carbon city. We adopt an ecological economics lens to expose the limitations of the urban resource efficiency paradigm when tackling environmental degradation beyond city boundaries. Based on the interpretation of urbanisation as a material practice, we urge for a fundamental recalibration of sustainability paradigms in urban planning. To integrate the impacts of urbanisation on non-urban landscapes within the framework of urban sustainability science, we furthermore stress the urgent need for frugality, resource reduction, and inclusiveness in urban planning practice.